Has structural economic vulnerability decreased in Least Developed Countries? Lessons drawn from retrospective indices - Joël Cariolle; Michaël Goujon; Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
Monitoring of structural change in Least Developed Countries (LDCs) requires examination of the changes in their structural economic vulnerability. This cannot be done by comparing the level of the Economic Vulnerability Index (EVI) that is calculated for each triennial review of the list of LDCs, because of the change in the design of the index. In this paper, the change in the structural vulnerability of LDCs is assessed according to two retrospective series of EVI, based on constant definitions, those respectively used at the 2006 and 2012 reviews. The real change in structural economic vulnerability is thus isolated from the impact of the changes in the design of the index (components, weighting, methods of calculation, and data updating).According to both retrospective series, structural vulnerability is not only markedly higher in LDCs than in other developing countries, but it shows a later and smaller decline over the period 1990-2011. The declining trend of EVI is due mainly to the trend of the shock sub-index which is more marked in non-LDCs than in LDCs according to both designs. On the other hand, the exposure trend, which declines at a similar rate in LDCs and non LDCs, seems to result from two factors which do not reflect a real structural change in LDCs: a higher population growth and a less rapid increase of the share of population located in low elevation areas.Moreover the change in 2012 of the weighting of the exposure index, together with the addition of the low elevation coastal zone (LECZ) component (at the expense of population size), introduced a bias into the distribution of vulnerability values within the LDC group. It works against dry land countries, which are often threatened by climate change. It also leads to underestimate the increase in the gap between the structural vulnerability of LDCs and non-LDCs.
Keywords: O11; C82; 330